Psychometric Properties of the Hospital Ethical Climate Survey: A Cross-Sectional Study in Greek and Cypriot Cancer Care Settings - Charalambous, Andreas; Cloconi, Constantina; Papastavrou, Evridiki; Adamakidou, Theodoula (My University, 2018)
Background and Purpose: Ethical climate provides the context in which ethical behavior and decision-making occur. To test the psychometric properties of the Greek version of the Hospital Ethical Climate Survey (HECS) in cancer care settings. Methods: This was a cross-sectional study with 235 cancer nurses. Principal component analysis (PCA) and confirmatory factor analysis (CFA) were examined. Reliability was investigated with Cronbach's coefficient a. Results: Cronbach's α was 0.86 for the HECS total and ranged from 0.71 to 0.85 for the five subscales. PCA revealed that five components accounted for 61.09% of the variance which were comparable to those produced in the original validation study. The CFA with the five factors identified, produced a model with a good fit. Conclusion: The Greek version of the HECS is valid and reliable for use within the cancer care context.
Keywords: Cancer patients; Cancer setting; Ethical climate; Reliability; Validation